1991
DOI: 10.1016/0042-6822(91)90760-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus (HEV): Molecular cloning and sequencing of the full-length viral genome

Abstract: We have recently described the cloning of a portion of the hepatitis E virus (HEV) and confirmed its etiologic association with enterically transmitted (waterborne, epidemic) non-A, non-B hepatitis. The virus consists of a single-stranded, positive-sense RNA genome of approximately 7.5 kb, with a polyadenylated 3' end. We now report on the cloning and nucleotide sequencing of an overlapping, contiguous set of cDNA clones representing the entire genome of the HEV Burma strain [HEV(B)]. The largest open reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
774
1
10

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 979 publications
(811 citation statements)
references
References 43 publications
(28 reference statements)
5
774
1
10
Order By: Relevance
“…All these biophysical characteristics suggest that HEV is similar to caliciviruses, as other investigators have suggested (Arankalle et al, 1988;Bradley et al, 1988). Reyes et al (1990) have recently reported that HEV might be a new virus of the Caliciviridae family, and Tam et al (1991) suggested that HEV represents either the prototype member of an as yet unclassified novel virus family or perhaps a separate genus within the Caliciviridae. Success in cultivating HEV in a human cell line in our laboratory will facilitate further research on HEV.…”
Section: Discussionmentioning
confidence: 54%
“…All these biophysical characteristics suggest that HEV is similar to caliciviruses, as other investigators have suggested (Arankalle et al, 1988;Bradley et al, 1988). Reyes et al (1990) have recently reported that HEV might be a new virus of the Caliciviridae family, and Tam et al (1991) suggested that HEV represents either the prototype member of an as yet unclassified novel virus family or perhaps a separate genus within the Caliciviridae. Success in cultivating HEV in a human cell line in our laboratory will facilitate further research on HEV.…”
Section: Discussionmentioning
confidence: 54%
“…IgG and IgM anti-HEV was detected with commercial assays (HEV Elisa and HEV IgM Elisa, Genelabs Diagnostics, Singapore Science Park). RT PCR was performed using the GeneAmp 9600 Thermocycler with primers targeting HEV ORF2 nucleotides 6,653-7,100 as described previously [Tam et al, 1991;Grandadam et al, 2004].…”
Section: Diagnosismentioning
confidence: 99%
“…It occurs in both epidemic and sporadic forms in most developing countries of Asia (1,2), Africa (3) and Latin America (4). The mortality of acute HEV infection ranges from 0.5-1% among the general population to as high as up to 20% in pregnant women (5).…”
Section: Introductionmentioning
confidence: 99%